2019
DOI: 10.3390/rs11111370
|View full text |Cite
|
Sign up to set email alerts
|

Sub-Pixel Crop Type Classification Using PROBA-V 100 m NDVI Time Series and Reference Data from Sentinel-2 Classifications

Abstract: This paper presents the results of a sub-pixel classification of crop types in Bulgaria from PROBA-V 100 m normalized difference vegetation index (NDVI) time series. Two sub-pixel classification methods, artificial neural network (ANN) and support vector regression (SVR) were used where the output was a set of area fraction images (AFIs) at 100 m resolution with pixels containing estimated area fractions of each class. High-resolution maps of two test sites derived from Sentinel-2 classifications were used to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 34 publications
0
12
0
Order By: Relevance
“…However, the generalized lithological maps generated from various fractional images engenders often difficulties in producing homogeneous maps [19], [20], and also produce an inconsistent generalized thematic results [21]. This technique is seldom applied in lithological mapping but widely used in crop mapping [22], [23]. It was acknowledged in previous studies [24], [25], that a pixel is not the optimal spatial unit for lithological mapping.…”
Section: Introductionmentioning
confidence: 99%
“…However, the generalized lithological maps generated from various fractional images engenders often difficulties in producing homogeneous maps [19], [20], and also produce an inconsistent generalized thematic results [21]. This technique is seldom applied in lithological mapping but widely used in crop mapping [22], [23]. It was acknowledged in previous studies [24], [25], that a pixel is not the optimal spatial unit for lithological mapping.…”
Section: Introductionmentioning
confidence: 99%
“…Immitzer et al [9] confirmed the high values of the red-edge and shortwave infrared (SWIR) bands for vegetation mapping but the usage of these raw bands additionally improved the classification tasks in comparison with those achieved by single index-based classification studies. Dimitrov et al [10] too used Sentinel-2 as training data to apply sub-pixel classification to PROBA images with a resolution of 100 m/pixel. The chosen machine learning methods, i.e., SVM and RF, provided classification accuracies ranging from 67% for grasslands to 92% for broad-leaved forests.…”
Section: State Of the Artmentioning
confidence: 99%
“…For instance, Saini et al [7] tested single-date images from Sentinel-2 using support vector machines (SVMs) and Random Forest (RF) and showed that the OA's of the classifications achieved by RF and SVM using one Sentinel-2 image were 84.22% and 81.85%, respectively [7]. While some studies used only one image for classification [7][8][9][10][11][12][13], other researchers have preferred multi-temporal information [14][15][16][17][18]. A long short-term memory neural net (LSTM) achieved an overall accuracy of up to 89.7% with Sentinel-2 time series [19,20].…”
Section: Introductionmentioning
confidence: 99%
“…A long short-term memory neural net (LSTM) achieved an overall accuracy of up to 89.7% with Sentinel-2 time series [19,20]. Another study based on support vector regression (SVR) and artificial neural network (ANN) achieved classification accuracies of up to 92% for broad-leaved forests [18]. In general, the multi-temporal approach captures better spectral characteristics over the growing season and improves crop types distinction.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation